Pathogenic Yeasts - Ashbee, Ruth.; Bignell, Elaine M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Mycological studies of yeasts are entering a new phase, with the sequencing of multiple fungal genomes informing our understanding of their ability to cause disease and interact with the host. At the same time, the ongoing use of traditional methods in many clinical mycology laboratories continues to provide information for the diagnosis and treatment of patients. This volume reviews various aspects of pathogenic yeasts and what is known about their molecular and cellular biology and virulence, in addition to looking at clinical and laboratory findings. As each chapter is written by a leading expert in the field, this book summarizes in one volume much of the latest research on several pathogenic yeasts, including Candida, Cryptococcus, Malassezia and yeasts of emerging importance. The importance of laboratory diagnosis, antifungal susceptibility testing, antifungal resistance and yeast diseases in animals are reviewed.
Comparative Genomic Analysis of Pathogenic Yeasts and the Evolution of Virulence -- Molecular Epidemiology of Candida Species -- Candida Infections and Modelling Disease -- Candida albicans Cell Wall Mediated Virulence -- Secreted Candida Proteins: Pathogenicity and Host Immunity -- Yeast Biofilms -- Cryptococcus: Spectrum of Disease and Treatment -- Typing Species of Cryptococcus and Epidemiology of Cryptococcosis -- Environmental Stress-Sensing and Pathogenicity in Cryptococcus neoformans -- Malassezia -- Emerging Systemic Yeast Pathogens -- Yeast Pathogens of Domestic Animals -- Laboratory Diagnosis of Yeast Infections -- Antifungal Susceptibility Testing and Therapy -- Mechanisms of Multidrug Resistance in Fungal Pathogens.
Keywords: Life sciences; Biodiversity; Microbiology; Life Sciences; Eukaryotic Microbiology; Microbiology; Biodiversity